Vejrforholdene i Landbrugsaaret 1904—1905. (Fra 1. Oktober 1904 til 30. September 1905.) - Willaume-Jantzen, V. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i Landbrugsaaret 1904—1905. (Fra 1. Oktober 1904 til 30. September 1905.)